Dampak Pertambangan Batubara Dalam Kehidupan Sosial Ekonomi Masyarakat di Desa Sempayau Kecamatan Sankulirang Kabupaten Kutai Timur - Losina Akaresti (Sekolah Tinggi Ilmu Ekonomi Bisnis dan Perbankan, 2022)
The issue addressed by this research is the influence of coal mining on the socioeconomic lives of the residents of Sempayau Village, Sangkulirang District, East Kutai Regency. The research technique is a descriptive cauldron, and the research informants include the Head of Sempayau Village, the Secretary of Sempayau Village, community leaders, and the residents of Sempayau Village. Among the methods of data collection are observation, interviews, and documentation. Data analysis is comprised of data reduction, data presentation (data display), and conclusion/verification drawing. The data's validity includes source triangulation, technique triangulation, and study time extension. The impact of coal mining on the socio-economic life of the community in Sempayau Village, namely the existence of coal mining, has a positive impact on the socio-economic life of the Sempayau Village community, including the availability of jobs for the local community, thereby assisting the local economy.The issue addressed by this research is the influence of coal mining on the socioeconomic lives of the residents of Sempayau Village, Sangkulirang District, East Kutai Regency. The research technique is a descriptive cauldron, and the research informants include the Head of Sempayau Village, the Secretary of Sempayau Village, community leaders, and the residents of Sempayau Village. Among the methods of data collection are observation, interviews, and documentation. Data analysis is comprised of data reduction, data presentation (data display), and conclusion/verification drawing. The data's validity includes source triangulation, technique triangulation, and study time extension. The impact of coal mining on the socio-economic life of the community in Sempayau Village, namely the existence of coal mining, has a positive impact on the socio-economic life of the Sempayau Village community, including the availability of jobs for the local community, thereby assisting the local economy.